ANALISIS PROSES PEMBELAJARAN IPA BERORIENTASI PADA ASPEK AKHLAK, KEILMUAN DAN KEPEMIMPINAN DI SEKOLAH ALAM INDONESIA PALEMBANG - Ermawati, Ermawati; Hastiana, Yetty; Seri, Herman (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study, aimed to determine, the science learning process oriented to the aspects of moral, knowledge, and leadership at Sekolah Alam Indonesia (SAI) Palembang. The, research, method used, is descriptive qualitative using a case, study approach. The,research subjects consisted,,of science teachers, as well as students, in grades VII and VIII.. The data, were collected, using interview, observation, and documentation. Then, the data was analyzed, using. the Miles, and Hubermen model. The resultsn showedb that the science learning process carried out at SAI Palembang could be carriedd out in thee classroom or outsidee the classroom. Inn addition, the,method used,by the teacherris in the formmof lectures,qquestions andaanswers, discussions, presentations aand observations of the school environment, using learning resources in thee form off books and thee internet. The learning model applied is exploring the surrounding nature, and the learning mediaa is in tthe fform of learning videoss and the school environment. The implementation of the moral, scientific, and leadership aspects is more emphasized on the implementation of programs and activities that have been designed at the beginning of each semester. Kata kunci: proses pembelajaran, sekolah alam